Poverty Dynamics in Vietnam, 2002-2006 - Baulch, Bob; Dat, Vu Hoang (World Bank, Hanoi, 2017)
This paper provides a descriptive and multivariate analysis of poverty dynamics in Vietnam using panel data from the Vietnam household living standards surveys of 2002, 2004, and 2006. Transition matrices and contour plots confirm that while large numbers of households moved out of poverty between these years, many did not move far the poverty line and that around a tenth of rural households appear to be trapped in chronic poverty. Different categorical models are then estimated to analyze the correlates of chronic poverty and the drivers of poverty transitions in rural areas. Initial conditions, such as household size and composition, whether the household head comes from an ethnic minority or failed to complete primary school, and residence in northern Vietnam, have important roles in trapping households in poverty. Simultaneous quintile regression models show the chronically poor are more disadvantaged by geography and ethnic minority status, while changes in household size and the share of children matter more to the living standards of the never poor.